Implementation of Legal Protection Against The Criminal Acts of Children & Witnesses in The Criminal Action of Stealing - Meta Permatasari; Umar Ma'ruf (Law Development Journal, 2021)
The method used in this research is sociological research methods. This approach is directed at the setting and the individual holistically (intact). So, in this case it is not permissible to isolate individuals or organizations into variables or hypotheses, but it is necessary to see them as part of a whole. The purpose of this research is to analyze and explain: 1) The factors that encourage children to commit the crime of theft in the jurisdiction of the Semarang City District Attorney, 2) Implementation of Legal Protection for Child Perpetrators and Witnesses in the Crime of Theft in order to realize the principle of best interests Children in the Semarang City District Attorney, 3) Factors that hinder the implementation of legal protection for child perpetrators and witnesses in the crime of theft in order to realize the principle of the best interests of children in the Semarang City District Attorney and what is the solution. The results showed that The factors that encourage children to commit criminal acts of theft include: family, education, economy, social factors. The implementation of legal protection for children of perpetrators and witnesses in criminal acts of theft, namely by making efforts to resolve children's cases outside the judicial process, preventing children from being deprived of liberty, encouraging the public to participate and instilling a sense of responsibility to children. Factors that hinder the legal protection of children of perpetrators and witnesses in criminal acts of theft, namely: the investigation procedure file submitted by the investigator to the public prosecutor does not completely and clearly describe the perpetrator and victim in the occurrence of a criminal act.